FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PEMANEN SAWIT PADA PT. BIO NUSANTARA TEKNOLOGI, BENGKULU - Nainggolan, Ronika; Purwoko, Agus; Yuliarso, M. Zulkarnain (Jurnal AGRISEP, 2012)
Maintaining and promoting the development of agricultural sector must not be separated from the role of plantation sub-sector development. Plantation sub-sector which is part of the national development and one of the most important commodity in Indonesia’s economy is palm oil. This research was executed at the palm oil harvesting workers in PT. Bio Nusantara Teknologi, Bengkulu regency on April – May 2010. The purposes of this research were: (1) to count the productivity of the palm oil harvesting workers and (2) to analyze the factors that influence the productivity of the palm oil harvesting workers in PT. Bio Nusantara Teknologi Bengkulu. The amount of 121 daily payment workers was taken from 10 afdelling by stratified random sampling. The research showed that the productivity of the palm oil harvesting workers was 130,314 kg/day. While, factors that affected the productivity of the palm oil harvesting workers were workers’ age and the amount of burden dependency family.